Physiological Responses, Essential Oil Yield, and Active Constituents of Peppermint (Mentha × piperita L.) as Influenced by Graduated Water Stress - Al-Fahdawi, Hiba Jomaa; Salih, Ghada Saad (American Journal of Biology and Natural Sciences, 2026)
The present study was carried out at the Research Station of the College of Agriculture, University of Tikrit, during the 2024–2025 growing season to investigate the effect of different water stress levels on physiological and biochemical responses, essential oil production and menthol accumulation in peppermint (Mentha × piperita L.). The experiment was laid out in Randomized Complete Block Design (RCBD) with four irrigation treatments: T1 (100% FC), T2 (75% FC), T3 (50% FC) and T4 (25% FC) and three replications. Results showed that severe stress (25% FC) significantly reduced plant height, biomass, chlorophyll content, and stomatal conductance, while essential oil percentage increased significantly (P≤0.05). Menthol content reached its highest level under moderate stress (50% FC) at 48.3%. This study provides a local scientific database to support sustainable peppermint production under semi-arid climatic conditions of the Tikrit region.